Single, immediate postoperative instillation of chemotherapy in non-muscle invasive bladder cancer: a systematic review and network meta-analysis of randomized clinical trials using different drugs - Kang, Minyong (Oncotarget, 2016)
We performed a network meta-analysis of randomized controlled trials (RCTs) to compare the efficacy of several intravesical chemotherapeutic (IVC) agents after transurethral resection of bladder tumor (TURB) in non-muscle invasive bladder cancer patients. The literature search was conducted using the Embase, Scopus and PubMed databases for RCTs, including patients with single or multiple, primary or recurrent stage Ta or T1 urothelial carcinoma of the bladder managed with a single, immediate instillation of IVC after TURB. Thirteen RCTs met the eligibility criteria. Pair-wise meta-analysis (direct comparison) showed that pirarubicin [hazard ratio (HR): 0.31], epirubicin (HR: 0.62), and MMC (HR: 0.40) were the most effective drugs for reducing tumor recurrence. Bayesian network meta-analysis (indirect comparison) revealed that treatment with pirarubicin (HR: 0.31), MMC (HR: 0.44), or epirubicin (HR: 0.60) was associated with prolonged recurrence-free survival. Among the drugs examined, only pirarubicin reduced disease progression compared to controls. These results suggest that a single, immediate administration of IVC with pirarubicin, MMC, or epirubicin is associated with prolonged recurrence-free survival following TURB in non-muscle invasive bladder cancer patients, though only pirarubicin also reduced disease progression.